Characterization of Epoxy Resin Composite with Fire Kaolin at Different Temperatures - Suroor Noori Ismail; Muna Noori Ismael; Hazim Faleh Hassan; Farah Jawad Kadhum (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This pioneering study investigates epoxy resin’s mechanical properties and thermal conductivity, specifically exploring the effects of kaolin powder fired at (550 ºC and 925 ºC). Epoxy resin composite was formed by blending epoxy with (5, 10, 15, 5, 20) wt—% of kaolin powder to create a range of specimens. Fourier transform infrared (FTIR) spectroscopy analyses were performed to understand the interaction between kaolin powder and matrix material. Parameters such as flexural strength, impact strength, shore D hardness, and thermal conductivity were measured on the prepared samples. The results demonstrate that including kaolin powder in the polymer produces a progressive enhancement in flexural strength, impact strength, shore D hardness, and thermal conductivity.